Rede Blockchain para rastreabilidade de queijos artesanais no Brasil utilizando Hyperledger Fabric - Ricardo, Fernando Salhab Doria (Universidade Federal de São Carlos, 2024)
The artisanal cheese market in Brazil presents a promising and growing scenario, with an estimated revenue of US$10 million in 2021 and an annual growth projection rate of 2.04% until 2025, according to Sebrae - SC. However, this market faces considerable challenges, such as the strict sanitary requirements for producers and the lack of traceability in the food production chain. To overcome this last obstacle, the implementation of a blockchain network using the Hyperledger Fabric platform is proposed. This solution allows for the creation of a secure and transparent traceability system, enabling the recording and verification of all stages of the production chain. All stakeholders in this supply chain will have access to a Progressive Web App (PWA) platform, compatible with any device, whether desktop or mobile, making it easier to track and monitor the activities. The end consumer will be able, through a QR code printed on the packaging, to access the history of the cheese, ensuring the product’s origin, authenticity and safety. Throughout this work, the solution was implemented and several tests were simulated to ensure the system’s functionality and performance, paving the way for future research and eventual implementation in real market conditions.
Blockchain network for traceability of artisanal cheeses in Brazil using Hyperledger Fabric
Keywords: Queijos artesanais; Rastreabilidade; Cadeia de abastecimento; Blockchain; Hyperledger Fabric; PWA Progressive Web Application; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO